Mercados culturais no Brasil: o BNDES e o financiamento das empresas culturais brasileiras - Elder P. Maia Alves (Ciências Sociais Unisinos, 2017)
Over the past decade, the Brazilian Development Bank (Portuguese: Banco Nacional de Desenvolvimento Econômico e Social, abbreviated: BNDES) has become the main financial agent of the Brazilian companies specialized in the cultural sector. Throughout the expansion of household expenditure on goods, services and cultural activities, especially between 2004 and 2014, the Brazilian Development Bank extended its actions, services, financial products for cultural undertakings, plotting this way to a branched financial and institutional network that directly involves those Brazilian companies in the cultural sector operating in certain chains of creation, production, distribution and commercialization of artistic and cultural, digital and entertainment activities, notably in the context of audiovisual, editorial and property segment. This aspect has produced a fairly significant injunction within Brazilian cultural fields, once, until 2006, the largest development bank in Latin America, BNDES, was related to cultural fields only through the regular use of federal laws for Cultural Incentives, as the Rouanet Law, and it did not provide its main financial products, at reduced long-term interest rates, straight away to specialized private cultural undertakings, which comprise long value chains and also harbor the vast majority of workers and professionals in the cultural sector. Such changes have led BNDES to a range of new financial and institutional activities, which, together, turned it into the most important state actor in the market of cultural capitalism in Brazil.